The influence of stage of development and sowing depth on seed quality and seedling emergence of Gliricidia sepium - Iji, P.A.; Tarawali, G.; Baba, M. (1993)
Investigations were conducted into the development characteristics and influence of stage of pod development on seed viability of Gliricidia sepium. The influence of sowing depth on seedling emergence of the first and last harvests was also investigated. Pods were harvested over three periods - 57,67 and 77 days after initiation of flowering and the seeds extracted. A fourth set of seeds was obtained from pods that shattered in situ, about 87 days after initiation of flowering. Pod length and number of seeds per pod decreased while seed weight increased with stage of development. These differences were highly significant. Germination occured in seeds harvested at all stages although germinations were highest in seeds of later harvests. Seedling emergence was shorter in the more mature seeds than in the seeds from the first harvest. Gliricidia sepium seeds could be harvested at any period from 70 days after initiation of flowering without determinant to viability. This will ensure high seed recovery rates and purity. Sowing to less than 2 cm depth would perhaps, encourage higher rates of emergence.